Effect of Diosgenin in Suppressing Viability and Promoting Apoptosis of Human Prostate Cancer Cells: An Interplay with the G Protein-Coupled Oestrogen Receptor? - Figueira, Marília I (2024)
Diosgenin is a phytosteroid sapogenin with reported antitumoral activity. Despite the evidence indicating a lower incidence of prostate cancer (PCa) associated with a higher consumption of phytosteroids and the beneficial role of these compounds, only a few studies have investigated the effects of diosgenin in PCa, and its mechanisms of action remain to be disclosed. The present study investigated the effect of diosgenin in modulating PCa cell fate and glycolytic metabolism and explored its potential interplay with G protein-coupled oestrogen receptor (GPER). Non-neoplastic (PNT1A) and neoplastic (LNCaP, DU145, and PC3) human prostate cell lines were stimulated with diosgenin in the presence or absence of the GPER agonist G1 and upon GPER knockdown. Diosgenin decreased the cell viability, as indicated by the MTT assay results, which also demonstrated that castrate-resistant PCa cells were the most sensitive to treatment (PC3 > DU145 > LNCaP > PNT1A; IC50 values of 14.02, 23.21, 56.12, and 66.10 µM, respectively). Apoptosis was enhanced in diosgenin-treated cells, based on the increased caspase-3-like activity, underpinned by the altered expression of apoptosis regulators evaluated by Western blot analysis, which indicated the activation of the extrinsic pathway. Exposure to diosgenin also altered glucose metabolism. Overall, the effects of diosgenin were potentiated in the presence of G1. Moreover, diosgenin treatment augmented GPER expression, and the knockdown of the GPER gene suppressed the proapoptotic effects of diosgenin in PC3 cells. Our results support the antitumorigenic role of diosgenin and its interest in PCa therapy, alone or in combination with G1, mainly targeting the more aggressive stages of the disease.